Workstation‒Operator Interaction in 4.0 Era: WOI 4.0. Issue 11 (2018) - Cohen, Yuval; Golan, Maya; Singer, Gonen; Faccio, Maurizio
Abstract: Currently machine operator interface is mainly focused on providing the operator with easy control over the production processes and easy access to related information. However, myriad of recent technological advances in variety of fields including AI, raise the question of what could be added to the operator-machine interaction capabilities and how. This article explores the possibilities to harness new capabilities in cognitive and behavioral knowledge as well as AI and "Industry 4.0" literature in order to outline the architectural framework and capabilities of future work-station‒operator interaction as a principal component of the human‒machine interaction in the "Industry 4.0" era. The proposed system is named "Workstation‒Operator Interaction 4.0" (WOI 4.0). The equipment's capabilities allows an adaptive ongoing interaction that aims to improve operator performance, safety, well-being, and satisfaction, as well as production measures. The paper describes the main elements of the proposed WOI 4.0 architecture, and illustrates a case of smart machine‒operator interactions. The contributions, limitations, and implications of the proposed WOI 4.0 system in the "Industry 4.0" arena are discussed, and future research directions are presented.